Pelatihan literasi media untuk remaja - Rahesli Humsona; Sri Yuliani; Rutiana Dwi Wahyunengseh; TA Gutama; Atmanto Heru (Unri Conference Series: Community Engagement, 2021)
The use of digital media with pornographic video content will result in the disruption of adolescents both physically and mentally. Some conditions can also be experienced by teenagers, including: experiencing a dilemma, namely feeling guilty but feeling addicted, doing imitation (imitation), watching porn videos that encourage teens to imitate sexual acts, disrupted the process of sex education, difficult to concentrate on learning to disrupt their identity , and closed, inferior and not confident. The purpose of this training is to improve media literacy among teenagers. The method used is to adopt action research with 3 stages, planning, action, and fact finding. At the planning stage, the activity begins with identifying the knowledge and experiences of adolescents about the use of gadgets, as well as the experiences of adolescents related to pornographic content. Furthermore, in the action stage, they were given training to improve the correct understanding of the healthy use of media and how to avoid the dangers of pornography. The results of the activity showed that participants' knowledge of the media increased. Participants become aware of the dangers of pornography, they were more confident and empowered to avoid the negative impacts of using smartphones or gadgets. Participants also put forward some suggestions on the topics they are interested in for the next training. At the end of the activity at the fact finding stage, an evaluation is carried out to find out the shortcomings in the activity process.